Stress And Strength Analyses Of Ultra-Light Aircraft Fuselage - Saironi, Muhammad Isa (Universiti Sains Malaysia, 2021)
Ultra-light aircraft is a special kind of low-speed general aircraft. It is low weighted and small-sized however can depart and land without changing the structure of any parts. This thesis is the case study on the stress and strength analyses of an ultra-light aircraft fuselage about its performance dependent on a guideline from the Federal Aviation Administration under Federal Aviation Regulation (FAR) that has been provided to the operators of ultra-lights in the United States. This archive additionally gave a detailed method in dissecting the stress and strength of the fuselage of an ultra-light aircraft and the point-by-point design of the fuselage. The fuselage structure is intended to invigorate better weight proportions as the focal part of the body of an ultra-light aircraft. This project utilizes composite material as the chose material. The determination of material readies to withstand the load applied to the fuselage structure. The simulation analysis is finished by utilizing one of the Computer-aided Design (CAD) which is SolidWorks 2020 ×64 Edition software. The examination is performed to see whether the structure of the fuselage can uphold the applied load or neglect to convey the required base on the few kinds of simulation testing. Other than the simulation analysis, the analytical methodology is additionally determined to look at and check the structure of the fuselage. Mostly, maximum stress and fatigue failure strength is calculated on two critical points on the ultra-light aircraft fuselage which is on the tail dragger of the ultra-light aircraft fuselage and at the bracket connector between the landing gear and mainframe fuselage. The maximum equivalent von Mises stress calculated on the fuselage model is 550.80 MPa whereas the maximum principal stress is 574.03 MPa happen in case study 2. Besides, the maximum compressive buckling stress calculated on the fuselage model is 709.77 MPa happen in case study 2. In finishing this project, the material and equipment utilized in fabricating this fuselage are accessible in the Aerospace Structure Lab, School of Aerospace Engineering, Universiti Sains Malaysia, Engineering Campus.